(6 do potęgi 8 * 6 do potęgi 5)³ ; (6 do potęgi 6 ) do potęgi 5
----------------------------------------------------------------------------------------------- =
5 * (6²)do potęgi 4+ (6 do potęgi 4 )²


proszę pomuszcie


Odpowiedź :

Odpowiedź:

(6^8 * 6^5)³ ; (6^6 )^5  = (6^13)³ : 6^30 = 6^39 : 6^30 = 6^9

----------------------------------------------------------------------------------------------- =  6^0 = 1

5 * (6²)^4 + (6^4 )² = 5 * 6^8 + 6^8 = 6^8(5 + 1) = 6^8 * 6 = 6^9

Szczegółowe wyjaśnienie:

[tex](6^8 * 6^5)^3 / (6^6 )^5 \\ (6^13)^3 / 6^{30} \\ 6^{39} / 6^{30} = 6^9\\.\\5 * (6^2)^4 + (6^4 )^2 \\\\5 * 6^8 + 6^8 \\ 6^8(5 + 1) \\ 6^8 * 6 = 6^9\\\\\\\\ =6^9/ 6^9= 6^0 = 1[/tex]

mam nadzieje ze pomogłam.